MODEL OF INTERACTION BETWEEN FUNGI AND THE IMMUNITY OF BANANA PLANT - Rahmadina, Alfina
Fungi is one of the pathogens that can cause disease in banana plants. Diseased banana plants can cause a decrease in the quality of banana plants which then causes a decrease in banana yields. Banana plants have a two-layered immuned system, namely PTI (PAMP-triggered immunity) and ETI (effector-triggered immunity). This final project models the interaction between the fungus and the immune system in banana plants to review the dynamics that occur between the fungus and the immune system in banana plants. The first model considers only the PTI immune response and the second model views both PTI and ETI immune responses. Numerical simulation is carried out to find out the dynamics that occur at a certain time when only the PTI immune response is activated and when the PTI and ETI are both activated. Numerical simulations were also carried out to determine the most influential parameters on the defense response mechanism by the immune system in banana plants. The numerical simulation results show that for certain parameter values, banana plants can be prevented from disease depending on the initial conditions the fungus first infects banana plants.